HIV EPIDEMIC HETEROGENEITY IN ZIMBABWE: EVIDENCE FROM SUCCESSIVE DEMOGRAPHIC AND HEALTH SURVEYS. Issue 6 (15th January 2018) - Oseni, Zainab; Seedat, Farah; Kandala, Ngianga-Bakwin
Summary: Zimbabwe has one of the worst HIV epidemics in the world. This study investigated data from two successive Zimbabwe Demographic and Health Surveys (ZDHS) conducted in 2005–06 and 2010–11. A random representative sample of 30, 000 men aged 15–59 and women aged 15–49 was selected from the two surveys. The HIV prevalence was mapped with a flexible, coherent regression framework using a geo-additive semi-parametric mixed model. HIV indicator prevalence maps were constructed at the regional level, and at the administrative level relevant for policy design, planning and decision-making. Substantial regional variation was found, not only in the burden of HIV, but also in its risk factors. The results suggest that responses/policies should vary at the regional level to ensure that the often diverse needs of populations across a country are met and incorporated into planning the HIV response. The use of geographically referenced data in two successive ZDHS provides crucial new insights into the spatial characteristics of the HIV epidemic in Zimbabwe. In particular, it highlights the HIV heterogeneity across Zimbabwe, with substantial regional variation, not only in the burden of HIV, but also in its risk factors.